2021
DOI: 10.1002/pd.6066
|View full text |Cite
|
Sign up to set email alerts
|

What's out there for parents? A systematic review of online information about prenatal microarray and exome sequencing

Abstract: Objective:To identify what online patient information (presented in English) is available to parents about prenatal microarray (CMA) and exome sequencing (ES), and evaluate its content, quality, and readability.Method: Systematic searches (Google and Bing) were conducted, and websites were categorised according to their purpose. Websites categorised as patient information were included if they were: in English, directed at patients, or were a text, video, or online version of an information leaflet. Author-dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…However, several parents from our (highly educated) cohort commented that written information they received about pES was difficult to understand, signalling an urgent need to develop more accessible patient information. In other areas of prenatal testing, trials of web‐based decision aids have shown promise for enabling informed decisions 28,29 but to our knowledge no such tool currently exists for pES 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several parents from our (highly educated) cohort commented that written information they received about pES was difficult to understand, signalling an urgent need to develop more accessible patient information. In other areas of prenatal testing, trials of web‐based decision aids have shown promise for enabling informed decisions 28,29 but to our knowledge no such tool currently exists for pES 30 …”
Section: Discussionmentioning
confidence: 99%
“…In other areas of prenatal testing, trials of web-based decision aids have shown promise for enabling informed decisions 28,29 but to our knowledge no such tool currently exists for pES. 30…”
Section: Described By Health Professionals Described By Parentsmentioning
confidence: 99%